2021
DOI: 10.1097/psy.0000000000001032
|View full text |Cite
|
Sign up to set email alerts
|

Interpersonal Emotion Dynamics in Couples With Somatic Symptom Disorder: Dyadic Coherence in Facial Temperature During Emotional Interactions

Abstract: Supplemental digital content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…6 12 54 60 63 64 Researchers have a general concern for cognitive function, and five studies showed that patients with SSD have worse attention, memory and diseased cognition. 26 59 65–67 Regarding emotional regulation, one study found that patients with SSD and their partners were dysregulated in dealing with each other’s negative emotions 68 ; another study 63 showed that patients with SSD had a lower ability to distinguish between their own emotions and somatic feelings than healthy controls, but showed no significant differences compared with healthy controls in identifying others' emotions, emotional arousal and responses.…”
Section: Resultsmentioning
confidence: 99%
“…6 12 54 60 63 64 Researchers have a general concern for cognitive function, and five studies showed that patients with SSD have worse attention, memory and diseased cognition. 26 59 65–67 Regarding emotional regulation, one study found that patients with SSD and their partners were dysregulated in dealing with each other’s negative emotions 68 ; another study 63 showed that patients with SSD had a lower ability to distinguish between their own emotions and somatic feelings than healthy controls, but showed no significant differences compared with healthy controls in identifying others' emotions, emotional arousal and responses.…”
Section: Resultsmentioning
confidence: 99%
“…Frequency analysis of thermal signal permits of course to nd the single most informative components of the underlying phenomena, allowing to obtain a more detailed insight on the dataset. Indeed, it has been largely employed in the eld of thermal IR imaging applied on human studies [30][31][32] It is of fundamental importance to observe that the present work is highly innovative given that it is the rst time that a machine learning classi er relying on features extracted from a completely non-invasive and contactless technique has been used to segment the tumor area from the health tissue with outstanding performances.…”
Section: Discussionmentioning
confidence: 99%